Central administration of neuropeptide Y reduces the cellular heat stress response and may enhance spleen antioxidative functions in heat-exposed chicks. (27th July 2022) - Nishimura, Haruka; Wang, Ying; Elhussiny, Mohamed Z.; Tran, Phuong V.; Haraguchi, Shogo; Cockrem, John F.; Bungo, Takashi; Furuse, Mitsuhiro; Chowdhury, Vishwajit S.
Highlights: NPY lowered rectal temperature under control (CT) but not high (HT) temperatures. Central NPY reduced mRNA expression of HSP-70 in the spleen. Central NPY increased glutathione synthase mRNA expression in the spleen. Central injection of NPY enhanced plasma uric acid concentrations under high (HT) but not control (CT) temperatures. Abstract: Previously it was found that mRNA expression of neuropeptide Y (NPY) was increased in the chicken brain under heat stress. NPY has also been reported as an anti-stress factor to regulate brain functions in heat-exposed chicks. However, to the best of our knowledge, there is no report on the action of central NPY in the immune organs under heat stress. The aim of this study was to examine whether central injection of NPY can regulate heat stress response in the spleen and liver. After intracerebroventricular (ICV) injection of NPY, chicks were exposed to control thermoneutral temperature (CT: 30 ± 1 °C) or high ambient temperature (HT: 35 ± 1 °C) chambers for 60 min. Central injection of NPY caused lowering in rectal temperature under CT, but not under HT. Moreover, ICV injection of NPY caused a significant lower mRNA expression of heat-shock protein-70 and higher expression of glutathione synthase in the spleen, but not liver. Furthermore, plasma uric acid concentrations were significantly increased by the ICV injection of NPY in chicks under HT. These results indicate that brain NPY may contribute to attenuate the intracellular heat stress response and enhance antioxidative status in the immune organ, spleen in chicks.